INTEGRASI SAINS DALAM MATERI PEMBELAJARAN BAHASA ARAB PADA PERGURUAN TINGGI KEAGAMAAN ISLAM - Imelda Wahyuni (IAIN Kendari, 2016)
This paper discusses the integration of science in the preparation of learning materials in Arabic on Islamic Higher Education in Indonesia. Arabic learning is inseparable from the study of linguistics, particularly in understanding some of the terms related to the meaning attributed to the word